Effect of hypoalbuminemia on drug pharmacokinetics - Ilona Idasiak‐Piechocka; Dominik Lewandowski; Wojciech Świgut; Jörn Kalinowski; Klaudia Mikosza; Piotr Suchowiejski; Edyta Szałek; Agnieszka Karbownik; Miłosz Miedziaszczyk (2025)
Hypoalbuminemia, defined as serum albumin levels below 35 g/L, is common in patients with conditions such as nephrotic syndrome, cirrhosis, or sepsis. This review examines the impact of hypoalbuminemia on the pharmacokinetics of selected drugs-such as antibiotics, immunosuppressants, antifungals, or anticonvulsants-emphasizing its role in drug efficacy and safety. Albumin is the main drug transporter and key binding protein, which influences the free drug concentration and drug activity. The review includes all studies available in the scientific literature found in the PubMed, Scopus, and Cochrane databases. The paper emphasizes the importance of therapeutic drug monitoring (TDM) in patients with hypoalbuminemia to avoid subtherapeutic or toxic drug levels. Many drugs need for dose adjustments to achieve therapeutic levels, especially in critically ill patients. The results of studies emphasize the need for individualized dosing regimens based on TDM to optimize drug therapy in patients with hypoalbuminemia. Our review is the first article to summarize the influence of hypoalbuminemia on the pharmacokinetic parameters of drugs and may be a useful tool for clinicians in their daily work.